IMPLEMENTASI MODEL AUDITORY INTELLECTUALLY REPETITION BERBANTUAN MEDIA GEOBOARD BATIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IV SD - Fithroh Nor Aini; F Shoufika Hilyana; Savitri Wanabuliandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this study was to determine the increase in mathematical problem solving abilities in fourth grade students of SD 4 Honggosoco by applying the Auditory Intellectually Repetition Learning model assisted by Geoboard batik media. This study used Classroom Action Research (CAR), the subjects of this study were students in grade IV SD 4 Honggosoco Jekulo Kudus. With a total of 17 students consisting of 6 male students and 11 female students. Data collection techniques include interviews, observation, documentation and tests. The data analysis used is quantitative data analysis which includes student learning completeness and qualitative data analysis includes teacher teaching skills and student learning activities. The results obtained from the classroom action research showed that the implementation of the Auditory Intellectually Repetition model assisted by Geoboard batik media was able to improve students' mathematical problem solving abilities in mathematics class IV SD 4 Honggosoco. Learning with the Auditory Intellectually Repetition model assisted by Geoboard batik media is a new innovation for students to explore the concepts of perimeter and area of ​​squares and rectangles.